Albert Jäger (1801-1891) "Erinnerungen aus meinem Leben" Ein österreichischer Historiker als Chronist seiner selbst - Fliri, David (2023)
In this volume, the previously relatively unknown memoirs of the Austrian historian Albert Jäger (1801-1891) are published for the first time in a scholarly annotated edition. Through his long life, his multiple relationships and his various fields of activity as a clergyman, politician and scholar, Albert Jäger became a remarkable witness of his time. The memoirs offer special insights into the history of education and science, but also into the everyday, social and religious history of the Habsburg Monarchy in the 19th century.